Cytokine control of megakaryopoiesis. (4th July 2018) - Behrens, Kira; Alexander, Warren S.
Abstract: Platelets are anuclear blood cells required for haemostasis and are implicated in other processes including inflammation and metastasis. Platelets are produced by megakaryocytes, specialized cells that are themselves generated by a process of controlled differentiation and maturation of bone-marrow stem and progenitor cells. This process of megakaryopoiesis involves the coordinated interplay of transcription factor-controlled cellular programming with extra-cellular cues produced locally in supporting niches or as circulating factors. This review focuses on these external cues, the cytokines and chemokines, that drive production of megakaryocytes and support the terminal process of platelet release. Emphasis is given to thrombopoietin (Tpo), the major cytokine regulator of steady-state megakaryopoiesis, and its specific cell surface receptor, the Mpl protein, including normal and pathological roles as well as clinical application. The potential for alternative or supplementary regulatory mechanisms for platelet production, particularly in times of acute need, or in states of infection or inflammation are also discussed.